(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
The purpose of this paper is to critically examine the philosophical parallels between Heidegger’s existential philosophy and Zen Buddhism, as described in Dōgen’s classic essay ’Uji’. Part one of this paper describes Zen Buddhism’s radical approach to existential dilemmas and to understanding the ultimate nature of the self. Part two reviews Heidegger’s phenomenological descriptions of death and temporality. Part three represents a comparative analysis of both philosophies. It is proposed that, although there are clear similarities between Heidegger’s ontology and Zen philosophy, there are also profound differences. In this respect, Zen Buddhism emerges as a radical and most unique existential approach to understanding time, death and freedom, as well as the ultimate nature of suffering and the self.